Avaliação da estabilização de camas usadas na avicultura através de bioindicadores vegetais - Mendes, Pablo Machado (2011)
The society is currently moving in the direction of finding solutions to environmental problems that threaten the continuity of life on the planet, and these problems not caused exclusively by man, according to differing opinions of several scientists around the world. The poultry industry is one of the most striking of these food producers taking responsibility for going to meet the worldwide research trying to solve the problems of environmental pollution, the idea is proposing a viable solution both technically and economically and provide back a critical need in the field of creation of broiler chickens: the bed where the chicken are created is able to be discarded in agricultural land safely and without damaging the soil, in these case, without causing environmental impact on the ground? To answer this question we sought to evaluate the poultry litter in relation to their chemical composition, number of lots created on the poultry litter and biosecurity of these beds. Currently producers perform physical and chemical analysis to determine whether the bed can be designed in agricultural land, among them the C/N (carbon/ nitrogen), which is the main parameter to decide whether the bed can be considered stable and it ready for disposal. This study proposes to develop a test that serves as a bioindicator phytotoxicity to determine if a litter is ready to be allocated to agricultural soil without causing environmental impact to soil, water resources and the environment in general.